"But…I survived": A phenomenological study of the health and wellbeing of aging Black women in the Greater Toronto Area, Canada. (2nd January 2023) - Foster, Nicoda; Kapiriri, Lydia; Grignon, Michel; McKenzie, Kwame
Abstract: Studies that assess the association between race and health have focused intently on the cumulative impact of continuous exposure to racism over an extended period. While these studies have contributed significantly to the general understanding of the life experiences and health status of racialized people, few studies have explicitly bridged the experiences of aging with gender and the wide structural barriers and social factors that have shaped the lives of racialized older women. This study aimed to investigate the origins of health inequities to highlight factors that intersect to affect the health and wellbeing of older Black women across their life course. Descriptive phenomenology was used to describe older Black women's health and wellbeing, and factors that impact their health across their life course. Criteria-based sampling was used to recruit study participants ( n  = 27). To be eligible women needed to be 55 years or older, speak English, self-identify as a Black female, and live in the Greater Toronto Area. Data analysis was guided by phenomenology. Themes identified demonstrated that participants' health and wellbeing were influenced by gender bias, racism, abuse, and retirement later in life. Participants reported having poor mental health during childhood and adulthood due to anxiety and depression. Other chronic illnesses reported included hypertension, diabetes, and cancer. Qualitative methods provided details regarding events and exposures that illuminate pathways through which health inequities emerge across the life course.